Medicinski diskurz o imperativu naravnega znotraj kontracepcije na primeru prekinjenega spolnega odnosa - Simetinger, Gabrijela (Socialno delo, 2014)
The aim of the study was to determine gynaecologists' views and opinions on the imperative of the natural within contraception in the case of coitus interruptus. A qualitative study on contraception and coitus interruptus, which included 27 semi-structured in-depth interviews with gynaecologists from various geographical parts of Slovenia, was carried out between December 2010 and May 2011. Many gynaecologists believe in the imperative of the natural and trust natural methods of contraception, where they also place coitus interruptus. Due to their personal views and opinions, a significant number of gynaecologists, mainly female, still recommend natural methods of contraception despite the opposing medical doctrine. Thus, personal gynaecologists' views and opinions dominate when it comes to choosing a contraceptive method. Female gynaecologists proved to be carriers of traditional sexual culture by promoting traditional methods of contraception.
Keywords: ginekologi; seksualna kultura; spolna medicina; kontracepcija